The Benefits and Solution to the Challenges of Transit-Oriented Development (TOD) from Public Perspectives in KL Sentral: A Review - Bong, Adrian Yew Chung; Rosdi, Irna Nursyafina (Research in Management of Technology and Business, 2024)
Transit-Oriented Development (TOD) is introduced in Malaysia to promote the basis for urban land use planning to ensure viability of public transport based on the design and planning tactic. It brings various services such as social, economy and environmental benefits. Although TOD has brought variety of benefits, there are still challenges might be existed due to lack of stakeholder commitment and community involvement including facilities issues. Therefore, the research objectives are concerning the principle, benefits and challenges including solution to the challenges from public perspectives via a quantitative research method focusing in KL Sentral. The expected results aim to further elaborate the benefits and solution to the challenges for better understanding between public transportation users and TOD.